The technology of wafers and waffles. I, - Tiefenbacher, Karl F. (Academic Press is an imprint of Elsevier, 2017)
The Technology of Wafers and Waffles: Operational AspectsïÅ½is the definitive reference book on wafer and waffle technology and manufacture. It covers specific ingredient technology (including water quality, wheat flour, starches, dextrins, oils and fats) and delves extensively into the manufacturing elements and technological themes in wafer manufacturing, including no/low sugar wafers, hygroscopic wafers, fillings and enrobing. The book explains, in detail, operating procedures such as mixing, baking, filling, cooling, cutting and packaging for every type of wafer: flat and shaped wafers for making biscuits, ice cream cones, cups, wafer reels, wafer sticks (flute wafers) and biscuit wafers. It also explores the various types of European (Belgian) waffles and North American frozen waffles.
Keywords: Pancakes, waffles, etc.; Baked products.; Baked products industry.; elektronické knihy; electronic books